A focus on culture and leadership. (12th September 2019) - Foster, Sam
Abstract : Sam Foster, Chief Nurse, Oxford University Hospitals, discusses 'compassionate leadership', an approach that aims to allow staff to provide the best care for patients by listening to and acting on staff concerns